Does implicit theory of intelligence moderate judgment of learning-based study time allocation?. (February 2023) - Ikeda, Kenji; Jiang, Juming; Kakinuma, Kyosuke; Tanaka, Ayumi
Abstract: Prior research demonstrated that the theory of intelligence (TOI), which included incremental theory (intelligence is a malleable trait and develops incrementally) and entity theory (intelligence is a fixed and stable trait), affected metacognitive control processes. We focused on metacognitive control processes, such as study time allocation, and examined whether TOI moderated the relationship between judgments of learning (JOLs) and study time allocation (JOL-based study time allocation). In the experiments, participants were asked to remember word pairs and make JOLs during the initial study phase. Subsequently, they restudied these in a self-paced manner. Our results suggest that the TOI did not moderate JOL-based study time allocation. Experiment 1 showed that participants allocated more study time to lower JOLs items in a laboratory setting. Experiment 2 obtained similar results in an online setting. These results suggest that individuals devote more study time to poorly learned (lower JOLs) items, regardless of the TOI. Highlights: Theory of intelligence guides learning behavior and affects learning outcomes. Examined the relationship between theory of intelligence and judgments of learning-based study time allocation. Theory of intelligence did not moderate judgments of learning-based study time allocation. People allocated more study time to lower judgments of learning items, regardless of theory of intelligence.